Carbon fiber surface treatment process

Through melamine modification and nano-silica grafting technology, the problem of poor interfacial performance caused by carbon fiber surface defects is solved, and the mechanical properties of carbon fiber composite materials are significantly improved.

CN119553497APending Publication Date: 2025-03-04HYOSUNG CARBON MATERIALS (JIANGSU) CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411654584.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The chaotic graphite texture on the surface of carbon fiber makes it difficult to achieve good wetting and bonding effects with the polymer matrix, which in turn affects the interface characteristics and overall performance of the composite material, resulting in poor mechanical properties.

Method used

The nanosilica was carboxylated and modified by silane coupling agent KH550 and succinic anhydride, and the nanosilica was grafted to the surface of the carbon fiber to fill the surface defects.

Benefits of technology

By introducing amino groups and grafting nanosilicon dioxide, the interface and mechanical properties of carbon fibers are enhanced and the mechanical properties of carbon fiber composites are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The invention discloses a carbon fiber surface treatment process, which belongs to the technical field of organic synthesis, and comprises the following steps: S1, taking melamine, adding into tetrahydrofuran, adding carboxylated carbon fiber and a condensing agent, heating to 50-60 DEG C, stirring for 3-4 hours, washing, and drying to obtain melamine modified carbon fiber; s2, adding nano silicon dioxide into DMF (Dimethyl Formamide), performing ultrasonic treatment, adding a silane coupling agent KH550 and succinic anhydride, stirring for 3-5 hours, washing and drying to obtain modified silicon dioxide; and S3, adding the modified silicon dioxide into DMF, adding the melamine modified carbon fiber and a condensing agent, heating to 90-100 DEG C, stirring for 4-5 hours, washing, and drying to obtain the surface-treated carbon fiber. The silane coupling agent KH550 and butanedioic anhydride are used for carboxylation modification of nano silicon dioxide, melamine is used as a coupling agent, nano silicon dioxide is grafted on carbon fibers, surface defects on the surfaces of the carbon fibers can be filled, and therefore the mechanical performance of the carbon fibers is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fiber materials, and in particular relates to a carbon fiber surface treatment process. Background Art

[0002] Carbon fiber is transformed from organic fiber through a series of heat treatment processes. Because its carbon content exceeds 90%, it exhibits excellent physical and chemical properties, such as high modulus, high strength, low density, light weight, chemical corrosion resistance and high temperature resistance. It is widely used in material lightweighting, aerospace materials, sensing technology, wind turbine blades, electrical and thermal conductivity, infrastructure construction and other corrosion-resistant and high-temperature resistant protection and energy fields.

[0003] However, since the surface of carbon fiber exhibits a chaotic graphite texture, its surface is smooth and inactive, which makes it difficult to achieve good wetting and bonding between it and the polymer matrix, thereby adversely affecting the interface characteristics and overall performance of the composite material, resulting in poor mechanical properties of carbon fiber composites, which in turn makes it prone to brittle fracture during service.

[0004] Interface optimization is usually achieved by modifying the surface of carbon fiber. In the existing technology, chemical vapor deposition (CVD) is usually used to deposit modified materials onto the fiber surface. This has the advantage of high deposition density. However, the high temperature during the deposition process usually causes a significant decrease in the performance of the carbon fiber. Summary of the invention

[0005] In view of the above situation, in order to overcome at least part of the defects of the above-mentioned prior art, the present invention provides a carbon fiber surface treatment process.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a carbon fiber surface treatment process, comprising the following steps: S1, adding melamine to tetrahydrofuran, adding carboxylated carbon fiber and condensation agent, heating to 50°C-60°C, stirring for 3-4 hours, washing, and drying to obtain melamine-modified carbon fiber; S2, taking nano-silica and adding it to DMF, ultrasonically treating it, adding silane coupling agent KH550 and succinic anhydride, stirring for 3 hours to 5 hours, washing, and drying to obtain modified silica; S3, adding modified silica into DMF, adding melamine-modified carbon fiber and condensation agent, heating to 90°C-100°C and stirring for 4-5 hours, washing and drying to obtain surface-treated carbon fiber.

[0007] In some embodiments, the condensing agent is one of an onium salt condensing agent and an organic phosphorus condensing agent.

[0008] In some embodiments, the condensing agent is HATU among onium salt condensing agents.

[0009] In some embodiments, the mass ratio of the carboxylated carbon fiber, melamine and condensation agent in step S1 is 10:1-2:1-2.

[0010] In some embodiments, the particle size of the nano-silica in step S2 is 50 nm-100 nm.

[0011] In some embodiments, the mass ratio of nano-silica, silane coupling agent KH550 and succinic anhydride in step S2 is 50:2-3:4-6.

[0012] In some embodiments, the ultrasonic treatment in step S2 is performed for 20 min to 30 min and at a power of 200 to 300 W.

[0013] In some embodiments, the mass ratio of the melamine-modified carbon fiber, the modified silica and the condensation agent in step S3 is 20:4-7:4-6.

[0014] In some embodiments, the preparation method of the carboxylated carbon fiber is as follows: The carbon fiber is placed in a 68wt% concentrated nitric acid solution, reacted at 70°C-80°C for 2 hours-3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0015] In some embodiments, the carbon fiber is a polyacrylonitrile-based carbon fiber carbonized at high temperature and has a diameter of 6 μm-7 μm.

[0016] The beneficial effects achieved by the present invention are as follows: By modifying carbon fiber with melamine, a large amount of amino groups can be introduced on the surface of carbon fiber to enhance the interface properties of carbon fiber, thereby improving the mechanical properties of carbon fiber composites. Nano-silica is carboxylated by using silane coupling agent KH550 and succinic anhydride, and nano-silica is grafted onto carbon fiber using melamine as a coupling agent, which can fill the surface defects of the carbon fiber and thus improve the mechanical properties of the carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The tensile properties test results of Examples 1-8 and Comparative Example 1 of the present invention are shown in FIG. Figure 2 The interlayer shear performance test results of Examples 1-8 of the present invention and Comparative Examples 1 and 2 are shown in FIG. The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0020] In view of the deficiencies in the prior art mentioned in the background technology, the present invention proposes a synthesis process of tetraacetaldehyde, comprising the following steps: S1, adding melamine to tetrahydrofuran, adding carboxylated carbon fiber and condensation agent, heating to 50°C-60°C, stirring for 3-4 hours, washing, and drying to obtain melamine-modified carbon fiber; S2, taking nano-silica and adding it to DMF, ultrasonically treating it, adding silane coupling agent KH550 and succinic anhydride, stirring for 3 hours to 5 hours, washing, and drying to obtain modified silica; S3, adding modified silica into DMF, adding melamine-modified carbon fiber and condensation agent, heating to 90°C-100°C and stirring for 4-5 hours, washing and drying to obtain surface-treated carbon fiber.

[0021] Among them, melamine has a higher amino density and a lower price. Through melamine, a large number of amino groups can be introduced on the surface of carbon fiber at a lower cost, thereby enhancing the interface properties of carbon fiber and thus improving the mechanical properties of carbon fiber composites.

[0022] At the same time, nano-silica is carboxylated by using silane coupling agent KH550 and succinic anhydride, and nano-silica is grafted onto carbon fiber using melamine as a coupling agent, which can fill the surface defects of the carbon fiber surface and thus improve the mechanical properties of the carbon fiber.

[0023] In addition, a condensation agent is used to promote the reaction between the carboxylated carbon fiber and melamine, and between the modified silica and the melamine-modified carbon fiber.

[0024] It should be noted that DMF is N,N-dimethylformamide, which is used as a reaction solvent.

[0025] In some embodiments, the condensing agent is one of an onium salt condensing agent and an organic phosphorus condensing agent. Onium salt condensation agents such as HATU (O-(7-azabenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate), HBTU (O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate), BOP (benzotriazol-1-yloxytris(dimethylamino)phosphorus hexafluorophosphate) and PyBOP (1H-benzotriazol-1-yloxytripyrrolidino hexafluorophosphate), and organophosphorus condensation agents such as diphenylphosphoryl chloride (DPP-Cl), diethyl cyanophosphate (DECP), diphenylphosphoryl azide (DPPA), dimethylthiophosphoryl azide (MPTA) and bis(2-oxo-3-oxazolidinyl)phosphoryl chloride (BOP-Cl) have the advantages of high reactivity and good selectivity.

[0026] In some embodiments, the condensing agent is HATU among the onium salt condensing agents. Since HATU has higher activity, the reaction rate is faster when HATU is selected as the condensing agent.

[0027] In some embodiments, in step S1, the mass ratio of carboxylated carbon fiber, melamine and condensation agent is 10:1-2:1-2.

[0028] In some embodiments, the particle size of the nano-silicon dioxide in step S2 is 50nm-100nm. The smaller the particle size of the nano-silicon dioxide, the larger the specific surface area, the higher the reaction activity, and the easier it is to perform surface modification on it. At the same time, the worse the stability of the nano-silicon dioxide, therefore, the particle size of the nano-silicon dioxide needs to be controlled within 50nm-100nm.

[0029] In some embodiments, in step S2, the mass ratio of nano-silica, silane coupling agent KH550 and succinic anhydride is 50:2-3:4-6.

[0030] In some embodiments, the ultrasonic treatment in step S2 lasts for 20 min to 30 min and the power is 200 to 300 W. The ultrasonic treatment can disperse the nano-silicon dioxide in DMF, which is convenient for subsequent surface modification of the nano-silicon dioxide.

[0031] In some embodiments, in step S3, the mass ratio of melamine-modified carbon fiber, modified silica and condensation agent is 20:4-7:4-6.

[0032] In some embodiments, the preparation method of carboxylated carbon fiber is as follows: The carbon fiber is placed in a 68wt% concentrated nitric acid solution, reacted at 70°C-80°C for 2 hours-3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0033] The carbon fiber is subjected to surface oxidation treatment with concentrated nitric acid having strong oxidizing properties to impart oxygen-containing functional groups to the carbon fiber, thereby obtaining carboxylated carbon fiber, improving the surface chemical inertness of the carbon fiber, and enhancing its surface polarity.

[0034] In some embodiments, the carbon fiber is a polyacrylonitrile-based carbon fiber carbonized at high temperature, and has a diameter of 6 μm-7 μm.

[0035] The present invention will be further described below by way of specific embodiments.

[0036] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0037] Example 1 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 70°C for 2 hours, washed, and dried to obtain carboxylated carbon fiber.

[0038] Carbon fiber surface treatment: S1, take 5g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 5g of condensation agent HATU, heat to 50°C and stir for 3 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 20min at a power of 200W, add 0.4g of silane coupling agent KH550 and 0.8g of succinic anhydride, stir for 3 hours, wash and dry to obtain modified silica; S3. Add 4 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 4 g of condensation agent HATU, heat to 90° C. and stir for 4 hours, wash and dry to obtain surface-treated carbon fiber.

[0039] Example 2 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 70°C for 3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0040] Carbon fiber surface treatment: S1, take 5g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 5g of condensation agent HATU, heat to 50°C and stir for 3 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 20min at a power of 300W, add 0.4g of silane coupling agent KH550 and 0.8g of succinic anhydride, stir for 5 hours, wash and dry to obtain modified silica; S3. Add 4 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 4 g of condensation agent HATU, heat to 100° C. and stir for 5 hours, wash and dry to obtain surface-treated carbon fiber.

[0041] Example 3 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 73°C for 3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0042] Carbon fiber surface treatment: S1, take 7g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 7g of condensation agent HATU, heat to 52°C and stir for 4 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 30min at a power of 200W, add 0.5g of silane coupling agent KH550 and 0.9g of succinic anhydride, stir for 4 hours, wash and dry to obtain modified silica; S3. Add 5 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 5 g of condensation agent HATU, heat to 90° C. and stir for 4 hours, wash and dry to obtain surface-treated carbon fiber.

[0043] Example 4 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 73°C for 3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0044] Carbon fiber surface treatment: S1, take 7g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 7g of condensation agent HATU, heat to 52°C and stir for 4 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 30min at a power of 300W, add 0.5g of silane coupling agent KH550 and 0.9g of succinic anhydride, stir for 4 hours, wash and dry to obtain modified silica; S3. Add 5 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 5 g of condensation agent HATU, heat to 100° C. and stir for 5 hours, wash and dry to obtain surface-treated carbon fiber.

[0045] Example 5 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 76°C for 2 hours, washed, and dried to obtain carboxylated carbon fiber.

[0046] Carbon fiber surface treatment: S1, take 8g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 8g of condensation agent HATU, heat to 57°C and stir for 3 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 20min at a power of 200W, add 0.6g of silane coupling agent KH550 and 1.1g of succinic anhydride, stir for 3 hours, wash and dry to obtain modified silica; S3. Add 6 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 6 g of condensation agent HATU, heat to 90° C. and stir for 4 hours, wash and dry to obtain surface-treated carbon fiber.

[0047] Example 6 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 76°C for 3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0048] Carbon fiber surface treatment: S1, take 8g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 8g of condensation agent HATU, heat to 57°C and stir for 3 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 20min at a power of 300W, add 0.6g of silane coupling agent KH550 and 1.1g of succinic anhydride, stir for 5 hours, wash and dry to obtain modified silica; S3. Add 6 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 6 g of condensation agent HATU, heat to 100° C. and stir for 5 hours, wash and dry to obtain surface-treated carbon fiber.

[0049] Example 7 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 80°C for 2 hours, washed, and dried to obtain carboxylated carbon fiber.

[0050] Carbon fiber surface treatment: S1, take 10g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 10g of condensation agent HATU, heat to 60°C and stir for 4 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 30min at a power of 200W, add 0.4g of silane coupling agent KH550 and 1.2g of succinic anhydride, stir for 4 hours, wash and dry to obtain modified silica; S3. Add 7 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 4 g of condensation agent HATU, heat to 95° C. and stir for 4 hours, wash and dry to obtain surface-treated carbon fiber.

[0051] Example 8 Preparation of carboxylated carbon fibers: The carbon fiber was placed in a 68wt% concentrated nitric acid solution, reacted at 80°C for 3 hours, washed, and dried to obtain carboxylated carbon fiber.

[0052] Carbon fiber surface treatment: S1, take 10g of melamine and add it to 300mL of tetrahydrofuran, add 50g of carboxylated carbon fiber and 10g of condensation agent HATU, heat to 60°C and stir for 4 hours, wash and dry to obtain melamine-modified carbon fiber; S2, take 10g of nano-silica and add it to DMF, ultrasonically treat it for 30min at a power of 300W, add 0.6g of silane coupling agent KH550 and 1.2g of succinic anhydride, stir for 4 hours, wash and dry to obtain modified silica; S3. Add 7 g of modified silica into 200 mL of DMF, add 20 g of melamine-modified carbon fiber and 6 g of condensation agent HATU, heat to 95° C. and stir for 5 hours, wash and dry to obtain surface-treated carbon fiber.

[0053] Comparative Example 1 The difference between this comparative example and Example 1 is that the carbon fiber surface treatment step does not include step S2 and step S3, that is, nano-silica is not grafted, and melamine-modified carbon fiber is prepared.

[0054] Comparative Example 2 The difference between this comparative example and Example 1 is that only carboxylated carbon fibers are prepared without performing surface treatment on the carbon fibers.

[0055] Experimental Example 1 The carbon fiber tensile properties were tested on Examples 1-8 of the present invention and Comparative Example 1: According to the test standard ISO5079-1995, the tensile test of the monofilament fiber was carried out by a tensile strength tester with a force range of 100 cN, and the tensile strength was tested with a clamp length of 20 mm and a loading speed of 5 mm / min.

[0056] Figure 1 This is a tensile performance test result diagram. As shown in the figure, the tensile strength of Example 1 is 6130 MPa, and the tensile strength of Comparative Example 1 is 4560 MPa. It can be seen that the tensile strength of carbon fiber is greatly improved after grafting nano-silica.

[0057] Experimental Example 2 The interlaminar shear performance (ILSS) of carbon fiber composite materials was tested for Examples 1-8 of the present invention and Comparative Examples 1 and 2. A carbon fiber composite material plate with a carbon fiber content of 60% was prepared using a matrix resin mainly composed of TDE-85 epoxy resin. The plate was cut into specified sizes according to the standard and then tested on a universal mechanical testing machine.

[0058] Figure 2 The interlaminar shear performance test results are shown in the figure. The interlaminar shear strengths of Example 1, Comparative Example 1 and Comparative Example 2 are 78.6 MPa, 64.7 MPa and 61.2 MPa, respectively. The interlaminar shear performance of Example 1 is improved to varying degrees compared with Comparative Examples 1 and 2.

[0059] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the protection scope of the present invention.

Claims

1. A carbon fiber surface treatment process, characterized in that: The steps include: S1, adding melamine to tetrahydrofuran, adding carboxylated carbon fiber and condensation agent, heating to 50°C-60°C, stirring for 3-4 hours, washing, and drying to obtain melamine-modified carbon fiber; S2, taking nano-silica and adding it to DMF, ultrasonically treating it, adding silane coupling agent KH550 and succinic anhydride, stirring it for 3 hours to 5 hours, washing it, and drying it to obtain modified silica; S3, adding modified silica into DMF, adding melamine-modified carbon fiber and condensation agent, heating to 90°C-100°C and stirring for 4-5 hours, washing and drying to obtain surface-treated carbon fiber.

2. The carbon fiber surface treatment process according to claim 1, characterized in that: The condensation agent is one of an onium salt condensation agent and an organic phosphorus condensation agent.

3. The carbon fiber surface treatment process according to claim 2, characterized in that: The condensing agent specifically adopts HATU among the onium salt condensing agents.

4. The carbon fiber surface treatment process according to claim 1, characterized in that: The mass ratio of the carboxylated carbon fiber, melamine and condensation agent in step S1 is 10:1-2:1-2.

5. The carbon fiber surface treatment process according to claim 1, characterized in that: The particle size of the nano-silicon dioxide in step S2 is 50nm-100nm.

6. The carbon fiber surface treatment process according to claim 1, characterized in that: The mass ratio of nano-silica, silane coupling agent KH550 and succinic anhydride in step S2 is 50:2-3:4-6.

7. The carbon fiber surface treatment process according to claim 1, characterized in that: The ultrasonic treatment in step S2 is performed for 20 min to 30 min at a power of 200 to 300 W.

8. The carbon fiber surface treatment process according to claim 1, characterized in that: The mass ratio of the melamine-modified carbon fiber, the modified silica and the condensation agent in step S3 is 20:4-7:4-6.

9. The carbon fiber surface treatment process according to claim 1, characterized in that: The preparation method of the carboxylated carbon fiber is as follows: The carbon fiber is placed in a 68wt% concentrated nitric acid solution, reacted at 70°C-80°C for 2 hours-3 hours, washed, and dried to obtain carboxylated carbon fiber.

10. The carbon fiber surface treatment process according to claim 9, characterized in that: The carbon fiber is a polyacrylonitrile-based carbon fiber that is carbonized at high temperature and has a diameter of 6 μm-7 μm.

Citation Information

Cited By

  • Carbon fiber with amine-containing molecules grafted on surface and preparation method and application thereof

    CN120250100A

  • Nano indium-iron microcrystalline adhesive and curing process

    CN120442199A

  • Carbon fiber connecting glue and curing process

    CN122648042A